Efektivitas Antibakteri Ekstrak Biji Alpukat (Persea americana Mill.) terhadap Pertumbuhan Bakteri Streptococcus mutans - Irma Sholekhah; Hidayati Hidayati; Didin Kustantiningtyastuti (Faculty of Dentistry Universitas Andalas, 2022)
Background : Streptococcus mutans bacteria are the main microorganisms that play an important role in the etiology of caries. Prevention of dental caries can be done by reducing the formation of plaque on the surface of the teeth, one of which is through the use of antibacterial compounds contained in avocado seed extract. Purpose : This study is to determine the antibacterial effectiveness of avocado seed extract in inhibiting the growth of Streptococcus mutans bacteria. Methods : This research method is an experimental laboratory with a post-test control group design. The avocado seed extract is made with a maceration technique with the result of a concentration of avocado seed extract of 100% then diluted using aquadest so that avocado seed extract concentrations of 10%, 15%, 20%, and 25% are obtained. The inhibitory test was done by Kirby-Bauer disk diffusion on Mueller Hinton Agar. The inhibition zone formed around the disc is measured using a caliper. The data analysis used was the One Way Anova test and continued with the Post Hoc LSD test. Results : The results showed that avocado seed extract at all concentrations can inhibit the growth of Streptococcus mutans bacteria. The largest inhibitory zone diameter at a concentration of 25% with a diameter of 12.25 mm and the diameter of the smallest inhibitory zone at a concentration of 10% at 10.48mm. the results of statistical analysis showed that there were significant differences between the inhibition zones of each avocado seed extract concentration (p<0.05).Conclusions : there is an effect of avocado seed extract (Persea americana Mill.) in inhibiting the growth of Streptococcus mutans bacteria with extract concentrations of 10%, 15%, 20%, and 25%.